Excellent outcomes of liver transplantation using severely steatotic grafts from brain‐dead donors. Issue 2 (February 2016) - Wong, Tiffany C. L.; Fung, James Y. Y.; Chok, Kenneth S. H.; Cheung, Tan To; Chan, Albert C. Y.; Sharr, William W.; Dai, Wing Chiu; Chan, See Ching; Lo, Chung Mau
Abstract : Liver grafts with macrovesicular steatosis of >60% are considered unsuitable for deceased donor liver transplantation (DDLT) because of the unacceptably high risk of primary nonfunction (PNF) and graft loss. This study reports our experience in using such grafts from brain‐dead donors. Prospectively collected data of DDLT recipient outcomes from 1991 to 2013 were retrospectively analyzed. Macrovesicular steatosis >60% at postperfusion graft biopsy was defined as severe steatosis. In total, 373 patients underwent DDLT. Nineteen patients received severely steatotic grafts (ie, macrovesicular steatosis >60%), and 354 patients had grafts with ≤60% steatosis (control group). Baseline demographics were comparable except that recipient age was older in the severe steatosis group (51 versus 55 years; P  = 0.03). Median Model for End‐Stage Liver Disease (MELD) score was 20 in the severe steatosis group and 22 in the control group. Cold ischemia time (CIT) was 384 minutes in the severe steatosis group and 397.5 minutes in the control group ( P  = 0.66). The 2 groups were similar in duration of stay in the hospital and in the intensive care unit. Risk of early allograft dysfunction (0/19 [0%] versus 1/354 [0.3%]; P >0.99) and 30‐day mortality (0/19 [0%] versus 11/354 [3.1%]; P  = 0.93) were also similar between groups. No patient developed PNF. The 1‐year and 3‐year overall survival rates in the severe steatosis group were both 94.7%. The corresponding rates in the control group were 91.8% and 85.8% ( P  = 0.55). The use of severely steatotic liver grafts from low‐risk donors was safe, and excellent outcomes were achieved; however, these grafts should be used with caution, especially in patients with high MELD score. Keeping a short CIT was crucial for the successful use of such grafts in liver transplantation. Liver Transpl 22:226‐236, 2016 . © 2015 AASLD.